ESTUARINE OCEANOGRAPHY OF THE VEMBANAD LAKE PART III: THE REGION BETWEEN COCHIN AND THE 3 0 M DEPTH OFF PORTMOUTH - Ramamirtham, C P; Muthusamy, S; Khambadkar, L R; Nandakumar, A; Kunhikrishnan, N P; Murty, A V S (Indian Journal of Fisheries, 2011)
The time-distribution patterns of temperature, salinity and oxygen content along the shipping channel from inside the port to a distance of about 15 km out into the Arabian sea during 1981-1983 are presented and discussed in this third and last part of the estuarine oceanographic study of the Vembanad lake. The distribution patterns show that hydrologically the nearshore region up to 12 or 15 km off Cochin is more or less identical to the adjacent coastal region, without having any apparent influence of the lake, during the dry months January to May. During the wet months, however, the discharge from the lake, characterized by suspended sediments, spreads as a plume, over highly saline and cold upwelled water, turning the region into an intermittent estuary. Though the end of the plume can often be pinpointed around the 30in depthline, by a sharp change of colour and filaments formed of floating objects of land and freshwater origin, the presence of an actual plume front is doubtful because of the weak surface convergence then occurring in a broad area off Cochin.